Influência de parâmetros no mecanismo das reações de reforma com vapor d'água e reforma oxidativa do etanol - Dancini-Pontes, Isabela (2017)
Socioeconomic and political problems caused by the environmental impacts of polluting and non-renewable energy sources have aroused an increasing interest for renewable and nonpolluting energy sources. Among the candidates for supplying this need is hydrogen. For hydrogen to fulfill the requirements for a renewable and clean combustible, its production line itself must have these characteristics. Ethanol reforming is an alternative hydrogen production process that meets these requirements. Nevertheless, despite the great number of investigations about this technology, ethanol reforming is a highly complex process and several points still need to be clarified. In this context, this work provides important information for a better comprehension of ethanol reforming. Inert and oxidative atmosphere tests were conducted with different catalytic supports with the aim of understanding the contribution of each of them to the process. Three CeO2 supports were tested one, of which was from commercial source and two others were calcined at different temperatures, namely, 550 and 800 oC. Moreover, Nb2O5 supports were tested in three different ways, namely, in pure form, impregnated with Na2O, and impregnated with CeO2. The CeO2 support calcined at 800 oC presented the smaller deactivation among the six tested supports, and it also presented the smaller flow rate of undesirable products, like ethene, acetone and CO. As for the Nb2O5 support impregnated with Na2O, considerable modifications in its characteristics were observed relative to the pure support. This doping propitiated less undesirable products, like ethene, and diminished coke formation. The study of the supports allowed us to suggest that ethene production and its polymerization are intimately connected to the concentration of hydroxyl groups on the surface, which were quantified by DTP -CO2 analyses. Moreover, the study conducted with the supports suggests that the oxidation reactions are catalyzed, that is, they are dependent on the catalyst employed. In addition to the support study, a statistical investigation was conducted to evaluate the contribution of the factors: active phase (Ni, Cu), O2/C2H5OH ratio, and temperature. It was observed that Ni and Cu favor the reactional route of ethanol reforming, decreasing the flow rate of parallel reaction products. Temperature increase acted in the same direction, favoring the ethanol reforming route - specifically, the methane reforming. The presence of oxygen influenced significantly some parallel reactions, like ethanol oxidation, ethene formation, and increasing of the CH4 flow rate. Finally, the information obtained in this work propitiated the production of a map of possible reaction routes for the studied system that can be helpful for further developments in this technology. In other words, the employed statistical method was innovative and brought significant contributions for the understanding of ethanol reforming.